2014
DOI: 10.1007/s00431-014-2408-1
|View full text |Cite
|
Sign up to set email alerts
|

Radical serotype rearrangement of carried pneumococci in the first 3 years after intensive vaccination started in Hungary

Abstract: Due to PCV vaccination, a complete serotype arrangement occurred also in Hungary. The old "paediatric" serotypes were replaced by serotypes 11A, 35F, 19A, 6B, 15B, 3 and 38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These latter data are available online, in Hungarian, reported annually by the National Bacteriological Surveillance Management Team of the National Public Health Center [72]. In case of S. aureus and S. pneumoniae, this difference has been observed also in our previous studies [18,39,40,73].…”
Section: Serotypesupporting
confidence: 69%
“…These latter data are available online, in Hungarian, reported annually by the National Bacteriological Surveillance Management Team of the National Public Health Center [72]. In case of S. aureus and S. pneumoniae, this difference has been observed also in our previous studies [18,39,40,73].…”
Section: Serotypesupporting
confidence: 69%
“…Also in Japan, as demonstrated in the present study, serotype 19A emerged as a dominant serotype after PCV7 introduction, showing the highest rate of isolates with both erm (B) and mef (A/E) among all the serotypes. Similarly, a high prevalence of these macrolide resistance genes in serotype 19A pneumococci was described in the United States, Europe and Asia (Taiwan) [27] , [28] , [29] , [30] , furthermore, macrolide-resistant pneumococci carrying both resistance genes were associated with multidrug resistance [31] , [32] . Thus, it is possible that such drug resistance traits of serotype 19A may be one of the reasons for persistence of this serotype even after introduction of PCV13.…”
Section: Discussionmentioning
confidence: 73%
“…Several surveys have documented the effect of PCV on NP carriage with conflicting results ( 10 , 11 , 12 ). The main reason for the unchanged prevalence of NP carriage is serotype replacement of non-vaccine types ( 13 , 14 ). After the introduction of PCV7, the incidence of pneumococcal disease and NP carriage due to NVTs, most notably for serotype 19A, increased incrementally.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NP carriage prevalence was found to be higher in children attending a day-care centre. In a study carried out in Hungary, the NP carriage rate among unvaccinated children attending a day-care centre was also found to be higher ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation